Motivation to participate in secondary science communication - Hu, Zhichen; Ma, Baolong; Bai, Rubing (Frontiers in Psychology, 2022)
The rise of social media provides convenient mechanisms for audiences to participate in secondary science communication (SSC). The present study employs the theory of consumption values and theory of planned behavior to predict audiences’ SSC intentions. The results indicate that emotional value, social value, altruistic value, attitude, internal perceived behavioral control and subjective norm are significant predictors of audiences’ intentions to share or to repost science content on their social media. These results suggest that the theory of consumption values, together with the theory of planned behavior, is a useful framework for understanding SSC behaviors.